The Influence of Islamic Business Ethics, Strategic Location, and Perceived Ease of Use on Consumer Satisfaction with the McDonalds Banda Aceh Drive-Thru Service - Alifah, Nisrina Nur; Nizam, Ahmad; Umuri, khairil Umuri; Amri, Amri; Elfida, Cut (Universitas Syiah Kuala, 2025)
The rapid growth of the fast-food industry in the era of globalization has intensified competition, compelling companies to deliver services that meet consumer needs and foster customer satisfaction. In Aceh, the establishment of McDonalds Banda Aceh is not only a business milestone but also a social phenomenon due to heightened public sensitivity toward business ethics and Islamic values amid global boycott movements. This study investigates the influence of Islamic Business Ethics, Strategic Location, and Perceived Ease of Use of drive-thru services on Consumer Satisfaction at McDonalds Banda Aceh. Using a quantitative causal approach, a Likert-scale questionnaire was distributed to 105 drive-thru consumers, and the data were analyzed through multiple linear regression after passing validity, reliability, and classical assumption tests. The findings show that the three independent variables simultaneously have a significant effect on consumer satisfaction, with an Adjusted R Square value of 0.536. Partially, Strategic Location has a positive and significant effect on consumer satisfaction, whereas Islamic Business Ethics and Perceived Ease of Use do not exhibit significant effects. These results indicate that easy accessibility, adequate parking space, and a safe and comfortable drive-thru environment are dominant factors shaping customer satisfaction. Overall, the study concludes that Strategic Location is the primary determinant of consumer satisfaction in the McDonalds Banda Aceh drive-thru service, while Islamic Business Ethics and Perceived Ease of Use have not yet emerged as decisive variables. The study implies that management should prioritize accessibility and drive-thru traffic management while continuously enhancing the service experience to maintain long-term customer satisfaction.